Interpretive Stories (Kwentong Bayan) of Sariaya, Quezon and Tourism as a Lived Experience - Rodriguez, Ma. Corazon P. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 7 No 1 (2011), 2011)
This paper discusses the experience of writing stories (kwentong bayan) or local narratives about a place and applying them to tourism packages. The stories were analyzed for themes and categories of culture elements from the research site in Sariaya, Quezon and were made part of community-based tourism packages aimed at students (identified as a target niche sector by the tourism council of Sariaya). These themes included the following: “religiosity of the Sariayahins”, “historicizing the present and living the past”, “spirit of community” and “gender, status and power relations”. The insights of the article explain the project team’s understanding of tourism as an activity that goes beyond merely visiting a place, so that it is also a meaningful experience for both locals and visitors (this was validated, for example, through out-of-classroom activities by UP students participating in homestay programs in Sariaya). Through the sharing of specific narratives and of ‘thick descriptions’ that expose diverse reflections on the particularities, nuances and contradictions of Sariaya culture and society, as articulated in written kwentong bayan by a local tourism volunteer and by researchers for the purposes of this paper, it is apparent that visitors can engage more closely with local reality and tourism can be an enriching and empowering experience for both insiders and outsiders.
Keywords: Culture; kwentong bayan; storytelling; tourism as a lived experience; Sariaya, Quezon